Comparative efficacy of pitavastatin and simvastatin in patients with hypercholesterolemia: a meta-analysis of randomized controlled clinical trials - Ma N; Cui LQ (Dove Medical Press, 2015)
Ning Ma,1,2 Lianqun Cui1 1Department of Cardiology, Shandong Provincial Hospital, Shandong University, 2Department of Cardiology, Heze Municipal Hospital, Heze, Shandong, People's Republic of China Background: Simvastatin is a statin used to lower low-density lipoprotein cholesterol, but has limitations in patients on complicated regimens due to concerns about drug-drug interactions. Pitavastatin is a newly developed statin with limited drug-drug interactions. We conducted a meta-analysis to compare the clinical efficacy of simvastatin and pitavastatin in the control of hypercholesterolemia.Methods: Randomized clinical trials comparing the efficacy of pitavastatin and simvastatin were identified by searching PubMed (2000–2014) and EMBASE (2000–2014). The primary outcome subjected to meta-analysis was percent change in low-density lipoprotein cholesterol compared with baseline.Results: Four clinical trials were selected for meta-analysis. A total of 908 patients treated with pitavastatin (2 or 4 mg/day) and 381 patients treated with simvastatin (20 or 40 mg/day) were included in the final statistical analysis. No statistically significant difference was identified between treatment with pitavastatin 4 mg/day and treatment with simvastatin 40 mg/day for 12 weeks (mean difference -0.66; 95% confidence interval -2.92, 1.61; P=0.57). Similarly, no statistically significant difference was observed between pitavastatin 2 mg/day and simvastatin 20 mg/day for 4 weeks (mean difference -2.19; 95% confidence interval -0.11, 4.49; P=0.06). Treatment with pitavastatin was noninferior to simvastatin in all of the secondary outcomes and the safety profile was similar between the two statins.Conclusion: Pitavastatin is noninferior to simvastatin in lowering low-density lipoprotein cholesterol.Keywords: pitavastatin, simvastatin, hypercholesterolemia, meta-analysis